Renin profiling predicts neurohormonal response to sacubitril/valsartan. (20th November 2020) - Vergaro, Giuseppe; Sciarrone, Paolo; Prontera, Concetta; Masotti, Silvia; Musetti, Veronica; Valleggi, Alessandro; Giannoni, Alberto; Senni, Michele; Emdin, Michele; Passino, Claudio
Abstract: Aims: Clinical trials and observational cohorts show that beneficial effects of sacubitril/valsartan are less strong in an appreciable proportion of patients with heart failure with reduced ejection fraction (HFrEF). Lower blood pressure and impaired renal function predict suboptimal sacubitril/valsartan titration and a less favourable response. Circulating renin encompasses neurohormonal activation, intravascular volume, and renal function. We hypothesized that renin may predict response to sacubitril/valsartan, assessed by changes in N‐terminal fraction of pro‐brain natriuretic peptide (NT‐proBNP). Methods and results: We performed a prospective, open‐label, real‐life cohort study. The study population consisted of 80 consecutive HFrEF patients (age 66 ± 10 years, 83% men) planned to initiate sacubitril/valsartan. Clinical and biohumoral assessment, including a full neurohormonal panel, was performed at baseline and at 1, 3, and 6 month follow‐up. Response to sacubitril/valsartan was defined as ≥30% reduction in NT‐proBNP levels from baseline to 6 months. Patients in the lower renin tertile had higher blood pressure and plasma sodium concentration (all P  < 0.05). At follow‐up, 38 patients (48%) were classified as responders. Circulating renin was lower in the responder group compared with non‐responders (19.8 mU/L, IQR 3.7–78.0 mU/L vs. 55.0 mU/L, IQR 16.4–483.1 mU/L; P  = 0.004). After adjustment for age, renal function, and blood pressure, renin was independently associated to response to sacubitril/valsartan ( P  = 0.018). Conclusions: In our preliminary study, we show that circulating renin predicts reduction in NT‐proBNP levels after sacubitril/valsartan initiation in HFrEF patients. Renin assessment might be useful to discriminate potential responders from the subgroup with a weaker expected benefit, thus needing a closer, tailored management strategy.